Chinese text segmentation for information retrieval - Li, Hui (2008)
Chinese word segmentation is a prerequisite process in Chinese information retrieval (IR) to divide the originally continuous sentences in the documents into linguistic units (normally words) that can then be indexed for the purpose of retrieval. Despite a host of word segmentation approaches and Chinese information systems that exist today, little work has been done to co-relate segmentation performance and IR effectiveness. Consequently, it is uncertain how word segmentation affects IR effectiveness.